KARAKTERISTIK TEMPE DARI BIJI LAMUN (Enhalus acoroides) MENGGUNAKAN KOMBINASI STARTER TEPUNG BERAS, TERIGU, DAN TEMPE KEDELAI - Silaban, Bernita Br; Tupan, Tupan; Lamani, Masita; Nanlohy, Esterlina E.E.M. (Jurnal Perikanan Unram, 2025)
The raw materials used for tempe production are highly diverse. In addition to soybeans, tempe can also be produced from seagrass seeds (Enhalus acoroides) using tempe starter culture. To accelerate fermentation, additional starters in the form of rice flour and wheat flour were used. This study aimed to determine the characteristics of tempe made from Enhalus acoroides seeds using rice flour and wheat flour starters in combination with soybean tempe flour. The ratio of soybean tempe flour to wheat flour (A1) and rice flour (A2) was 1:3. The combined starter was added at 20% of the total weight of seagrass seeds. The research employed an experimental method. The parameters analyzed included appearance, taste, aroma, and texture for subjective evaluation, and moisture content, protein, fat, ash, carbohydrate, calcium (Ca), iron (Fe), and lead (Pb) for objective analysis. The results showed that the use of wheat flour and rice flour starters combined with soybean tempe flour produced tempe with varied sensory values and chemical compositions. The sensory evaluation of Enhalus acoroides tempe yielded appearance scores ranging from 3,12 to 3,87 (like to very like), taste scores of 3,18-3,20 (like), aroma scores of 3,0-3,3 (like), and texture scores of 3,7-3,8 (very like). The chemical composition included moisture content ranging from 56,04-59,73%, ash 0,52-0,96%, fat 0,85-1,3%, protein 1,52-2,92%, carbohydrate 35,53-40,63%, calcium (Ca) 0,15-0,77 mg/L, iron (Fe) 8,22-8,73 mg/L, and lead (Pb) 0,002-0,125 mg/L. The use of rice flour starter contributed the most to the sensory characteristics, moisture, fat, protein, and iron content of tempeh, while the wheat flour starter was more dominant in increasing ash, carbohydrate, and calcium levels. The lead (Pb) content was also found to be below the maximum permissible limit, indicating that the tempeh produced in this study is safe for consumption.